Microplastic Content in the Digestion of Freshwater Mussels (Pilsbryoconcha exilis) at Different Depths in Koto Panjang Reservoir, Riau - Hutagalung, Hanna Margaretta; Budijono, Budijono; Hendrizal, Andri (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Microplastics are small pieces of plastic that can pollute the environment. This study aims to determine the types of microplastics in the digestion of freshwater kijing based on different stocking densities and water depths. This research was carried out from February to April 2024. Using the experimental method with a one-factor Group Random Design. Sampling of the kijing was observed after 2 weeks of laying according to the specified depth, and then the abundance of microplastics in the digestion of freshwater kijing was examined. Water quality parameters are measured by temperature, brightness, and pH. The study found five microplastic types: fiber, fragments, films, granules, and pellets. The most common type of microplastic found at all three different depths is the type of film. The microplastic abundance found at all three depths in order is 5.2, 5,4 and 6 particles/ind. From the ANOVA results, the depth has a p-value of 0.00850, which means that the p-value > 0.005 does not show any difference between depth data. While the p-value of the treatment is 0.00084, this means that the p-value of <0.005 is the difference between the treatment data. Treatments consisting of 1kg, 2kg, and 3kg had different abundance data in each treatment. This means that there are significantly different results by the treatment of microplastic abundance data in freshwater mussel